Impact of COVID-19 Pandemic and Vaccine Information To Stock Returns and Volatility in Indonesia - Prayoga, Agus Diemas; Kim, Sung Suk (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Abstract. Â This study was conducted to investigate how investor attention affects COVID 19 outbreak information and vaccines on stock returns and Indonesian stock market volatility. We used the Google Search Volume Index to measure outbreak information and investor attention to the COVID19 vaccine. The empirical results obtained showed that the search volume associated with COVID19 outbreak information had a negative impact on the return on days, and conversely the presence of COVID19 vaccine information had a positive impact. In addition, this study examined in relation to stock market volatility, denying that COVID19 outbreak information causes excessive volatility in the market in inverse proportion to COVID19 vaccine information that actually reduces market volatility. We conclude that it provides a positive feeling. Â Abstrak: Penelitian ini dilakukan untuk mengetahui bagaimana perhatian investor mempengaruhi informasi wabah COVID 19 dan vaksin terhadap return saham dan volatilitas pasar saham Indonesia. Kami menggunakan Indeks Volume Penelusuran Google untuk mengukur informasi wabah dan perhatian investor terhadap vaksin COVID19. Hasil empiris yang diperoleh menunjukkan bahwa volume pencarian terkait informasi wabah COVID19 berdampak negatif terhadap return on days, dan sebaliknya keberadaan informasi vaksin COVID19 berdampak positif. Selain itu, penelitian ini mengkaji dalam kaitannya dengan volatilitas pasar saham, menyangkal bahwa informasi wabah COVID19 menyebabkan volatilitas yang berlebihan di pasar berbanding terbalik dengan informasi vaksin COVID19 yang justru mengurangi volatilitas pasar. Kami menyimpulkan bahwa itu memberikan perasaan positif.